(untitled) (Revista Apotheke, 2025)
This research aims to examine the principles and functioning of the extension group Pintura e Afins, which operates as a space for study, practice, and reflection on contemporary painting. Affiliated with the State University of Paraná, Curitiba I/EMBAP Campus, the group upholds the notion that the collective studio constitutes a site for the production and circulation of artworks either in process or completed as well as a forum for theoretical discussion and reflection that contributes to individual artistic practice. Throughout the text, selected works and testimonials from some of its members are presented, highlighting how this experience strengthens artistic practice and opens pathways for new inquiries. Theoretical studies of Barry Schwabsky and David Salle, combined with conversations surrounding the creative process, consolidate both individual and collective practices, while establishing broader exchanges with contemporary artistic production.